Controlling jako przejaw aktywności innowacyjnej współczesnych przedsiębiorstw - Brojak-Trzaskowska, Małgorzata; Rzążewska, Aneta (Controlling as a sign of modern enterprises innovative activity, 2005)
Nowadays enterprise survival, its development and competitive advantage mostly depend on inspiring innovative projects, that should not be concentrate on products or processes, but every area of enterprise functioning. Present methods become less efficient. New management conceptions can be very helpful in increasing incomes and financial potential. Controlling ensures profitability and solvency. Moreover, controlling can provide enterprises with its survival on markets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 227-234